Social networked game dynamics in web 2.0 language learning communities - Katerina Zourou; Marie-Noëlle Lamy (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This paper critically examines the role of game dynamics facilitated by social networks, and their potential for language learning and peer support. The context of investigation is made up of four types of web 2.0 language learning communities. The design of game mechanics as incentives for digital activity across the community types is scrutinized in terms of the extent to which these mechanics support language learning, regarding learners' roles, expected behaviours and attitudes to language learning. We situate our analysis in the broader web 2.0 context and link it to the crowdsourcing trend (Howe, 2006) whereby, as two sides of the same coin, user engagement is fostered in an unrestricted and collaborative manner, and the latent talent of the crowd can then be exploited by commercial companies for no remuneration. Our findings show that game mechanics model user activity by following a sophisticated incentive-centred approach, not always made clear to users before entering these communities. The analysis clearly demonstrates that game mechanics are the driving force of overall online activity, targeting language learning although not exclusively, and that game mechanics may benefit language learning as well as the commercial interests of these communities supported by web 2.0 start-ups.